Silent Sympathy: News Attention, Subtle Support for Far-Right Extremism, and Negative Attitudes Toward Muslims - Knupfer, Helena (Terrorism and political violence, 2025)
Right-wing terrorist (RWT) incidents targeting Muslims have become more frequent and news reporting about these incidents can trigger a variety of cognitions and behaviors in audiences. While some studies report more tolerance and openness in response to RWT, hate crimes against minorities can increase in their aftermath. To date, we know little about the associations between following news reporting about RWT and attitudes toward Muslims as one of the main target groups of modern RWT. Using a young, quota-based German sample (aged 16–25, N = 865), we build on Terror Management and Social Identity Theory to shed light on the relationships between attention to RWT in the media, threat attributed to RWT, and negative attitudes toward Muslims. Additionally, a measure of subtle support for far-right extremist stances (SSE) was included, accounting for moderation effects. Results suggested that attention to RWT was positively related to perceived threat. This association was weaker in individuals with higher levels of SSE. Attributing more threat was associated with less negative attitudes toward Muslims, independent of SSE. Media attention only had a (positive) association with negative attitudes in individuals with moderate to high levels of SSE. Implications and limitations are discussed.